2023
DOI: 10.1055/a-2039-1728
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Electrochemical Cascade Cyclization Reactions

Abstract: This review highlights the recent progress in the electrochemical cascade cyclization reactions for the synthesis of carbon rings and heterocycles such as pyridines, quinolines, phenanthridines, cinnolines, 1,4-dihydroquinolines, oxindoles, imidazo[1,5-a]pyridines, imidazoles, etc. The works included herein are introduced in tow major sections of heterocycle construction and carbocycle construction reactions, covering the works reported from 2012 to 2022.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 146 publications
(244 reference statements)
0
7
0
Order By: Relevance
“…However, the advantages of electrochemical methods, such as sustainability and selectivity, make them a promising option with more applications in future research, complementing the established portfolio of traditional methods currently used in organic synthesis. [22][23][24] A schematic overview of significant parameters for organic electrosynthesis can be subcategorized into the following form, shown in Table 2. These parameters can all have a significant impact on the outcome of electro-organic synthetic reactions and should be carefully optimized to achieve the desired results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the advantages of electrochemical methods, such as sustainability and selectivity, make them a promising option with more applications in future research, complementing the established portfolio of traditional methods currently used in organic synthesis. [22][23][24] A schematic overview of significant parameters for organic electrosynthesis can be subcategorized into the following form, shown in Table 2. These parameters can all have a significant impact on the outcome of electro-organic synthetic reactions and should be carefully optimized to achieve the desired results.…”
Section: Introductionmentioning
confidence: 99%
“…However, the advantages of electrochemical methods, such as sustainability and selectivity, make them a promising option with more applications in future research, complementing the established portfolio of traditional methods currently used in organic synthesis. [22][23][24] Sahar Imeni was born in 1998 in Tehran (Iran). In 2022, she graduated with a master's degree in organic chemistry from Azad University (sciences and research) in Tehran.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29][30] Numerous studies focusing on electrochemical processes for C-C, C-N, and C-S bond formations have emerged in the past decade. [31][32][33][34][35][36][37][38][39][40][41] Recent years have witnessed an upsurge in electrochemical desulfurization/cyclization techniques contributing to the synthesis of diverse N-containing compounds like 1,2,4-thiadiazole rings, 42 1,2,4-triazole rings, 43 imidazole-fused N-heterocycles, 44 quinazolinones, 45 and thiazoles. 46 Additionally, our research group has reported the electrochemical synthesis of 2-aminobenzoxazoles through an iodide-mediated desulfurization-cyclization process in a one-pot fashion in aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen heterocycles are key structural frameworks found in significant fields, ranging from natural products, drugs, superconducting materials, energy storage materials, polymer materials to organic dyes, etc . 1,2 Among multifarious nitrogen-containing heterocycles, tetrahydrobenzo[ b ][1,8]naphthyridines are of great biological and pharmaceutical value. 3 On the other hand, as another type of nitrogen heterocycle, 7,8-dihydroquinolin-5-ones are also important skeleton components that exist in active molecules and natural products (Fig.…”
Section: Introductionmentioning
confidence: 99%